NUMERICAL SIMULATION STUDYONDRAGREDUCTIONTECHNOLOGYOF NON-SMOOTHSURFACEOF PIT - KUAI ChuTing; WANG WeiQiang; WU YuLiang; WANG Bo; Du ShengNan; WANG GuoFu (Jixie qiangdu)
For pipeline transportation,it is very important to reduce the transportation resistance consumption. In order to reduce the transportation resistance consumption,the application of non-smooth surface drag reduction technology is particularly important. By using the fluid mechanics knowledge and the numerical simulation software,establishing a pit theoretical model.The smooth surface and the pit surface with matrix arrangement were simulated and calculated based on the RNG k-ε model. Two kinds of surface flow fields were simulated respectively,and different drag reduction effects were obtained. Through calculation and analysis,we can conclude that under different working conditions,the surface of the pit with h = 0. 05 mm is better in drag reduction; analyzing the pit surface under 12 m·s-1 conditions,the average shear force is smaller than the smooth surface. Under the pressure difference,the fluid inside the pit generates a low-speed swirling gas,promotes the flow in the main flow region,and further reduces the total resistance.